Snake Bite Patterns, Management and Out-Come in Muzaffarabad, Azad Jammu & Kashmir - Nazir, Munazza Ul (International Journal of Pathology, 2019)
Background: Annual death rate attributed to snake bite accounts for 1.9 per 100,000 population in Pakistan. Southern parts of the country are affected the most; data is scarce from northern parts.Objectives: To study the patterns of snake bite, clinical features, management approach and out-come in Muzaffarabad, Azad Jammu & Kashmir (AJK).Methods: This was a descriptive observational study conducted from June 2017 to December 2018 at theDepartment of Internal Medicine, Sheikh Khalifa Bin Zayed Al Nahyan Hospital, Muzaffarabad, Azad Jammu & Kashmir. A detailed demographic and bite inquiry followed by thorough clinical examination was documented for each patient. This was followed by laboratory investigations including urinalysis, complete blood count, coagulation profile, renal function tests and ECG. Polyvalent snake Anti-venom as well as other supportive treatment was administered according to World Health Organization guidelines.Results: Out of 79 patients, 49 (62%) were females and 30 (38%) were males. Mean age was 33 years (SD±11.88). Fang marks were seen in 67 (84.8%). 48 patients (60.8%) were bitten between dusk to sunrise. Bite was on lower limb in 61 (77.2%) and upper limb in 16 (20.3 %). 75 (94.93%) had features of hemotoxic or cytotoxic envenomation comprising; local swelling or vesicles in 42 (53.1%), hypotension in 19(24.1%), epistaxis and hematuria in 11 (13.9%) and 16 (20.3%) respectively, prolonged prothrombin time and APTT in 41(51.9%) and 44 (55.7%) respectively. Raised serum creatinine and urea were observed in 52(65.8%) and 5 (6.3%) respectively. Symptoms of neurotoxicity were observed in 4(5.05%) patients. 2.5% (n=2) patients were placed on mechanical ventilator. 2.5% (n=2) patients did not survive the massive hemorrhagic diathesis.Conclusion: High incidence of hemotoxic and cytotoxic envenoming have been reported in district Muzaffarabad. Complete recovery is attributed to prompt general supportive treatment and specific treatment with antivenin therapy.